Religion and the sensation function - Ross, Christopher F.J. (Mental health, religion & culture, 2012)
The sensation function, a form of perceiving contrasting to the intuitive function in Jung's personality typology, is explored in reference to Van der Hoop's description of its distinct phenomenology: (1) a perceptual field in which details show up clearly but separately; (2) its association with two-sided, subject and object, transcendence. Implications are examined for individuals’ religious orientation when the sensation function is dominant or preferred, drawing on studies by pastoral theologians and spiritual directors, and the author's survey studies among Canadian Anglicans, Catholics and undergraduates in religious studies. Evidence is considered for the sensation function contributing to orientations to religion in the following forms: religion as (1) simplicity and presence, (2) providing direction, (3) practical service, (4) triggers to memory, (5) change avoidant, (6) preference for particular forms of prayer, and (7) a tendency to dichotomise. Conclusions focus upon the value of Jungian typology in providing an informed basis for differentiating a variety of religious pathways for psychological development, which may be useful to spiritually or religiously oriented individuals, and those who advise, guide, or teach them.